Emissão de gases de efeito estufa, características produtivas e morfológicas de cultivares de arroz sob manejos de irrigação - Nunes, João Angelo Silva (2019)
The cultivation of irrigated rice is an important source of greenhouse gases emission. Among the main greenhouse gases are the area of rice are methane (CH4) and nitrous oxide (N2O), which vary depending on crop management and irrigation management. The study of irrigation and cultivar management is of great importance as an alternative to increase productivity and grain quality without increasing planted area and water consumption. Rice plants have structures called aerenchyma, which mainly serve to oxidize the root system, but through these structures also the passage of other gases such as CH4 and N2O occurs. In this sense, the present study had as objective to quantify CH4 and N2O emissions, components of yield, grain quality, yield, morphological characteristics, partial global warming potential (pGWP) and index pGWP/grain yield (Yield-scaled) of rice cultivars under permanent irrigation and intermittent irrigation. In view of this, this thesis was structured in four chapters. Chapter 1 is a literature review entitled "Production, emission and methane mitigation measures in irrigated rice crops". The chapter 2 addresses the emission of CH4 and N2O, yield, global warming potential and global warming potential index for grain yield from areas of irrigated rice under the heading "Greenhouse gas emissions and global warming potential of rice cultivars under irrigation management". The chapter 3 deals with the morphological characteristics of the aerial part (number and diameter of stems and stature) of rice plants, as well as their internal structures (number, area and volume of aerenchyma and area and volume of the fistula) and dry mass production, this chapter is entitled "Structural characteristics of rice cultivars under irrigation management". The chapter 4 deals with the number of panicles per m2, the number of grains per panicles, the mass of a thousand grains, income of the benefit and on the physical characteristics of the grains (whole grains, plaster and white belly) and is titled "Performance components and grain quality of rice cultivars under irrigation management". From the results obtained, it was concluded that the cultivar XP 113 emits less methane and nitrous oxide, in addition to presenting higher grain yield, which guarantees, together with the cultivar Titan CL, lower Partial Global Warming Potential and lower pGWP/Grain Productivity. Intermittent irrigation, combined with low rainfall, adversely affects grain yield of rice, but results in lower methane emissions, pGWP and pGWP/GY. There is no difference in the emission of nitrous oxide as a function of irrigation management. The cultivar XP 113 shows a lower area and volume of aerenchyma, as well as a lower number of stems per m2 and dry mass of the aerial part, while the cultivar Lexus CL presents higher dry mass of aerial part, area and volume of aerenchyma and area and volume of fistula. There is a reduction in leaf area index when the rice plants are submitted to intermittent irrigation management in all cultivars, except for cultivar XP 113. The management of intermittent irrigation reduces plant height, shoot dry mass, area of aerenquimous and fistula) and volume (of aerenquimous and fistula). The cultivar IRGA 424 RI has a lower percentage of the cast area, of a thousand grain mass and of grains per panicle in relation to the other cultivars. The cultivars IRGA 424 RI and Titan CL have a higher percentage of whole grains. The cultivar XP 113 has a higher number of grains per panicle. Cultivars XP 113 and IRGA 424 RI have a lower percentage of grains and white belly. The management of intermittent irrigation does not reduce the sterility of spikelets, mass of a thousand grains, number of panicles per m2 and grain quality.